User guide to the four-square method for intervening in root, tuber and banana seed systems. RTB User Guide - Mulugo, L.; Ajambo, S.; Kikulwe, Enoch Mutebi (International Potato Center, 2021)
This guide presents a step-by-step procedure on how to use the four-square method for intervening in root, tuber and banana seed systems. The four-square method is a research tool that supports the generation of evidence on seed systems diversity so as to formulate interventions to conserve varieties and to improve availability, access, and quality of seed forvegetatively propagated crops (VPC). The tool consists of four squares that are drawn on either the ground or on a chart. Varieties of the crop of interest are mapped in each of the four squares based on their abundance i.e., Each square therefore represents either varieties grown by many households on large area, many households on small area, few households on large area or few households on smallarea. The data is collected in a participatory way using focus group discussions (FGDs) guided by questions that are framed according to the objectives of the study. The objectives could include, but no limited to, understanding local crop diversity, understanding the economic potential of crop varieties, setting breeding goals and developing plant breeding programs, determining impacts of seed interventions on crop varieties and monitoring crop variety diversity changes over time. Separate FGDs are often held for men and women to capture gender-specific perceptions. The social characteristics of FGD participants such as their age, marital status, level of education, and main occupation are also collected and used in the analysis. The tool can also be used to study on-going and completed seed system interventions.